Needs Analysis For Developing Problem-Based Learning E-LKPD Integrating Local Wisdom to Improve Mathematical Connection Skills - Evih Evih; Yusfita Yusuf; Margaretha Madha Melissa; Muhammad Hafidz Danujati Prayogo Yulianto (Journal of General Education and Humanities, 2026)
Mathematical connection skills constitute a core competency emphasised in the Independent Curriculum and by the National Council of Teachers of Mathematics (NCTM). Nevertheless, empirical classroom evidence reveals that these skills remain at a low level. This condition is paradoxical, given the increasing availability of digital infrastructure in schools, which has not been optimally integrated into mathematics learning practices. This study aims to identify the need to develop Problem-Based Learning (PBL)–based electronic student worksheets (E-LKPD) that integrate local wisdom, with a particular focus on uncovering the gap between technological availability and its pedagogical utilisation. This research adopts a Research and Development framework using the ADDIE model, limited to the needs analysis phase. Data were collected through teacher interviews, student and teacher questionnaires, and a mathematical connection skills test administered to 22 eighth-grade students at one of the junior high schools in Sumedang. The data were analysed using descriptive quantitative and qualitative techniques and validated through technical triangulation. The findings indicate that mathematics instruction continues to rely predominantly on textbooks and printed worksheets, despite the presence of adequate digital infrastructure. Both teachers and students expressed a strong need for interactive digital learning media that incorporate local wisdom within a PBL framework. Furthermore, students’ mathematical connection skills were found to be low, with an average score of 57.5 and only 27.3% achieving the minimum mastery criterion. These results underscore a significant discrepancy between infrastructure readiness and classroom practice, highlighting the urgency of developing PBL-based E-LKPD to foster students’ mathematical connection skills.